2008
DOI: 10.1080/13548500801983058
|View full text |Cite
|
Sign up to set email alerts
|

Birth order: Self-injurious and suicidal behaviour among adolescents

Abstract: A sample of 2553 children and adolescents in a psychiatry clinic in Germany were assessed using a structured interview inventory that included history of self-injurious behaviour, suicidal intent and socially disruptive and threatening behaviour, and diverse socio-demographic variables (the basis documentation or 'Ba-Do'). Birth order was associated with both suicidal and self-injurious behaviour, middle children being most likely to exhibit such behaviour. Females were more than twice as likely to have self-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…According to McGoldrick et al [ 31 ], a middle sibling position can be related to the risk of getting lost, being reserved, or feeling anxiety due to comparisons with younger and older siblings; thus, it can be assumed that middle siblings constantly fight for attention. Similar observations were made by Kirkcaldy, Richardson-Vejlgaard, and Siefen [ 43 ], who added that this relationship can be modulated by siblings. Obviously, these issues need to be studied further.…”
Section: Discussionsupporting
confidence: 84%
“…According to McGoldrick et al [ 31 ], a middle sibling position can be related to the risk of getting lost, being reserved, or feeling anxiety due to comparisons with younger and older siblings; thus, it can be assumed that middle siblings constantly fight for attention. Similar observations were made by Kirkcaldy, Richardson-Vejlgaard, and Siefen [ 43 ], who added that this relationship can be modulated by siblings. Obviously, these issues need to be studied further.…”
Section: Discussionsupporting
confidence: 84%
“…Early NSSI research primarily focused on understanding these behaviors in females, due to the assumption that females were more frequently affected than males [8, 9]. Variability in findings are evident, however, with some studies of adults indicating equal or higher prevalence in males when compared to prevalence rates in females [10, 11]. Similarly, within school-based adolescent samples, findings differ on rates across genders, with some data suggesting that gender differences occur more commonly in older adolescents [1214].…”
Section: Introductionmentioning
confidence: 99%
“…For example, higher rates of self-injurious (among males) and suicidal (among females) behavior were found to be highest among middle-born children in one large (N = 2,553) psychiatric sample (Kirkcaldy, Richardson-Vejlgaard, & Siefen, 2009). In this study, sibship size was also significantly (p < .0001) correlated to suicidal behavior.…”
Section: Firstborn Advantages and Vulnerabilities?mentioning
confidence: 73%
“…This association appears to be strong for both males and females with gender interactions typically not found (Briere & Elliott, 2003;Farrington, 2003;Krischer & Sevecke, 2008;Weiler & Widom, 1996;Weizmann-Henelius et al, 2010). At least one available study, however, has shown a gender by birth order interaction (described previously) on self-injurious behavior (Kirkcaldy et al, 2009). …”
Section: Gender Considerationsmentioning
confidence: 86%